Exploitation, exploration and innovation in a model of endogenous growth with locally interacting agents - Giorgio Fagiolo; Giovanni Dosi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
The paper presents a model of endogenous growth in which firms are modeled as boundedly-rational, locally interacting, agents. Firms produce a homogeneous good employing technologies located in an open-ended technological space and are allowed to either imitate existing, similar practices or to locally explore the technological space to find new, more productive techniques. We first identify sufficient conditions for the emergence of empirically plausible GNP time-series characterized by self-sustained growth. Then, we study the trade-off between individual rationality and collective outcomes by providing an example in which more rational agents systematically perform worse than less rational ones.
Keywords: 330; Innovation; Endogenous Growth; Local Interactions; Exploration vs. Exploitation